UPDATING EMISSION FACTORS FOR IN-USE MOTORCYCLES FUELED BY GASOLINE, E5 AND E10 IN VIETNAM - Pham Huu Tuyen; Pham Minh Tuan; Kazuhiro Yamamoto; Preechar Karin (My University, 2021)
Motorcycle is the most popular transportation means in Vietnam due to its low cost and flexibility. However, motorcycles emit substantial quantities of hydrocarbons, carbon monoxide, nitrogen oxides and some amount of particulate matter. Emission factors for in-use motorcycles in Vietnam were studied and established quite a long time ago. The objective of this study is to update the emission factors, not only gaseous emissions but also particle number, for in-use motorcycles in Vietnam. Ten carbureted and electronic fuel injected motorcycles representative for in-use motorcycles were selected for investigation. Each motorcycle was fueled by conventional gasoline, E5 and E10 in turn, and was tested on a chassis dynamometer according to ECE R40 driving cycle. The gaseous emissions were sampled and determined by standard methods, while the particle number in exhaust gas was sampled by using the sampling system developed by Laboratory of Internal Combustion Engine, Hanoi University of Science and Technology, Vietnam. The updated emission factors were then provided for carbureted motorcycles, EFI motorcycles and average motorcycle fleet in case of gasoline, E5 and E10 fueling.
Keywords: Kerosene; Driving cycle; Vehicle emissions and performance